Effect of Chlorine Plasma Treatment on Electronic Properties of GIZO Thin Film Grown on SiO2/Si Substrate - Dahlang Tahir; Suhk Kun Oh; Hee Jae Kang; Sung Heo; Jae Gwan Chung; Jae Cheol Lee (Journal of Mathematical and Fundamental Sciences, 2013)
The effect of chlorine plasma treatment on electronic properties of GIZO grown on SiO2/Si by RF magnetron sputtering was investigated using X-ray photoelectron spectroscopy (XPS), reflection electron energy loss spectroscopy (REELS), and secondary ion mass spectroscopy (SIMS). SIMS depth profiles indicated that the concentration of InO and ZnO on the surface was decreased after Cl2 plasma treatment. REELS data showed that the band gap increased from 3.4 to 3.7 eV. XPS showed that Ind5/2 and Zn2p3/2 shifted to the higher binding energies by 0.5 eV and 0.3 eV, respectively. These phenomena were caused by oxygen deficiency and hydrocarbon contamination reduction as indicated by Cl atom bonding with In and Zn cations that are present on the surface after Cl2 plasma treatment.